The Implementation of Character Education by Indonesian Language Teachers at MTsN 5 Blitar: Efforts to Instill Ethics and Morality in Students - Hidayati, Rizka Nabillah Nur; Mulyaningtyas, Rahmawati (UIR PRESS, 2024)
The decline in morale that occurs in the next generation of the nation is increasing. Character education can be done by anyone, one of which is an Indonesian teacher. The Indonesian teacher has the task of shaping the character of students because basically the Indonesian teacher has a role in the development of student communication. Thus, it is necessary to make efforts to instill character education in students by Indonesian teachers. The research method used in this study is a qualitative descriptive method. Data collection techniques used are observation, interviews, and documentation. The results of the study show that the efforts made by Indonesian teachers in shaping the character of students at MTsN 5 Blitar are carried out in four ways, namely through learning activities, exemplary activities, strengthening activities, and habituation activities. The obstacles faced by Indonesian teachers in instilling character education come from environmental influences and come from students themselves. And alternative solutions used by Indonesian teachers at MTsN 5 Blitar are teachers synergizing with all madrasah and family parties, strengthening school culture, teachers always giving moral messages.